중환자실 병상주변공간의 면적과 간격에 관한 연구 - 이현진; 권순정 (의료·복지 건축, 2019)
Purpose: This study tries to propose the dimensions and area related to patient bed and surroundings in ICU considering nurses’ observation and medical care. Methods: Literature survey, 11 Case studies, some Interviews with nurses and measuring of medical equipments’ dimension in ICU have been mobilized in order to deepen the ICU bed area standards. Results: 0.3m clearance between head wall and patient bed is necessary for emergency cases. The minimum distance at the foot of the bed should not be less than 0.9m for EMR cart and medical tray. The clear floor area of one bed and surroundings in open ward is 10.2㎡(3m×3.4m). In a single-bed patient room, the minimum clear floor area is 16.0㎡(4m×4m). Considering the control of cross infection in ICU, Single bed patient room is recommended. Implications: The result of this study can be applied to the design of ICU and legislation of ICU standard.
Keywords: Intensive Care Unit; Area around the bedside of ICU; Clearances around the bedside of ICU; Open Ward; Single Bed Patient Room; 중환자실; 중환자실 병상주변 면적; 중환자실 병상주변 간격; 개방형 병동; 1인중환자병실